Examination of the stability of the anxiety sensitivity index across the menstrual cycle in trauma-exposed women with and without PTSD. Issue 1 (2nd January 2020) - Nillni, Yael I.; Arditte Hall, Kim A.; Langdon, Kirsten J.; Pineles, Suzanne L.
ABSTRACT: Background and Objectives: Anxiety sensitivity (AS), as measured by the Anxiety Sensitivity Index (ASI), has consistently been studied as a trait-level predictor of a variety of emotional and physical health conditions, including premenstrual symptoms. The menstrual cycle influences symptom expression and stress reactivity among anxiety and stress-related disorders. However, research has yet to directly evaluate the stability of AS across the various phases of the menstrual cycle, particularly in clinical populations with high levels of AS and with documented menstrual cycle differences in symptoms such as women with posttraumatic stress disorder (PTSD). Design and Methods: The current study examined whether AS fluctuates as a function of menstrual cycle phase among a community sample of trauma-exposed women ( N  = 48) with and without PTSD. Participants completed the ASI, including subscales assessing sensitivity to physical, cognitive, and social symptoms of anxiety, during early follicular and mid-luteal menstrual cycle phases. Results: Results revealed that ASI scores remained relatively stable across the different phases of the menstrual cycle assessed; evidence for stability was particularly strong for the subscale assessing sensitivity to physical symptoms of anxiety. Conclusion: This study provides additional support for the conceptualization of AS as a stable, trait-like, cognitive risk factor.